2021
DOI: 10.1101/2021.08.25.457723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Multiple Types of Cancer Driver Mutations Using Targeted RNA Sequencing in NSCLC

Abstract: Currently, DNA and RNA are used separately to capture different types of gene mutations. DNA is commonly used for the detection of SNVs, indels and CNVs; RNA is used for analysis of gene fusion and gene expression. To perform both DNA sequencing (DNA-seq) and RNA-seq, material is divided into two copies, and two different proce-dures are required for sequencing. Due to overconsumption of samples and experimental process complexity, it is necessary to create an experimental method capable of analyzing SNVs, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, on the other hand, two samples with positive results by DNA‐NGS, failed to have RNA‐NGS results due to insufficient RNA quality, indicating the higher sample quality requirements of RNA‐NGS. Another study conducted head‐to‐head comparison of DNA‐NGS and RNA‐NGS in clinical formalin fixed paraffin embedded (FFPE) samples of 1253 NSCLC patients and found that 6% (10/168) of patients with negative results of DNA‐NGS oncogenic drivers test were rediscovered by RNA‐NGS detection (including 7 samples of fusion mutations, 3 samples of MET exon 14 skipping mutations), and these patients were offered targeted therapy [23].…”
Section: Level or Strength Evidence Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, on the other hand, two samples with positive results by DNA‐NGS, failed to have RNA‐NGS results due to insufficient RNA quality, indicating the higher sample quality requirements of RNA‐NGS. Another study conducted head‐to‐head comparison of DNA‐NGS and RNA‐NGS in clinical formalin fixed paraffin embedded (FFPE) samples of 1253 NSCLC patients and found that 6% (10/168) of patients with negative results of DNA‐NGS oncogenic drivers test were rediscovered by RNA‐NGS detection (including 7 samples of fusion mutations, 3 samples of MET exon 14 skipping mutations), and these patients were offered targeted therapy [23].…”
Section: Level or Strength Evidence Recommendationsmentioning
confidence: 99%
“…Using an NGS panel composed of a specific number of genes, typically covering at least 50 genes, is a feasible strategy. If no oncogenic drivers are detected by a DNA‐based NGS panel, RNA‐based NGS should be considered [23]. In addition to considering the number of genes, it is also important to consider the tiers of somatic variants on the covered genes.…”
Section: Level or Strength Evidence Recommendationsmentioning
confidence: 99%
“…On the one hand, gene expression data can indirectly reflect RNA-based protein expression levels, but cannot reflect gene sequence information, which SNV happens to reflect [11]. On the other hand, many diseases not only affect gene expression data, but more importantly, it is influenced by SNVs or even caused by SNVs [12,13]. Therefore, combining gene expression data and SNV data can better reveal the mechanism of action of diseases.…”
Section: Introductionmentioning
confidence: 99%